The association between sleep problems and general quality of life in cancer patients and in the general population - Hofmeister, Dirk; Schulte, Thomas; Mehnert-Theuerkauf, Anja; Geue, Kristina; Zenger, Markus; Esser, Peter; Götze, Heide; Hinz, Andreas (Frontiers in Psychology, 2022)
Objective: It is well-known that patients with cancer frequently experience sleep problems, and that sleep quality is associated with general quality of life (QoL). The aims of this study were to analyze the relationship between sleep problems and other components of QoL in more detail and to investigate sex and age differences in sleep quality in cancer patients in comparison with the general population. Method: This study comprised one general population sample (n = 4476) and eight samples with cancer patients (n between 323 and 4020). Sleep Quality was measured using the QoL questionnaire EORTC QLQ-C30. Results: All of the cancer patient groups reported more sleep problems than the general population. Sleep problems were associated with all facets of QoL both in cancer patients and in the general population. The highest associations were found in cancer patients for fatigue (r = 0.52) and emotional functioning (r = -0.47). The association between sleep quality and general QoL was lower in the cancer samples (r = -0.37) than in the general population (r = -0.46). Female cancer patients reported markedly more sleep problems than male patients did (d = 0.45), while this sex difference was lower in the general population (d = 0.15). In contrast to the general population, younger cancer patients had greater trouble sleeping than older patients did (d=-0,17). Conclusion: The results underline the significance of the role mental factors play in sleep problems. Health care providers should pay special attention to female patients and younger patients concerning this issue.